2010
DOI: 10.1038/ng.735
|View full text |Cite
|
Sign up to set email alerts
|

Common variants near ATM are associated with glycemic response to metformin in type 2 diabetes

Abstract: Metformin is the most commonly used pharmacological therapy for type 2 diabetes. We carried out a GWA study on glycaemic response to metformin in 1024 Scottish patients with type 2 diabetes. Replication was in two cohorts consisting of 1783 Scottish patients and 1113 patients from the UK Prospective Diabetes Study. In a meta-analysis (n=3920) we observed an association (P=2.9 *10−9) for a SNP rs11212617 at a locus containing the ataxia telangiectasia mutated (ATM) gene with an odds ratio of 1.35 (95% CI 1.22 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
217
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(229 citation statements)
references
References 36 publications
6
217
2
4
Order By: Relevance
“…The GoDARTS diabetic individuals were genotyped by either Affymetrix SNP6.0 chips (3673 patients) funded by the Wellcome Trust Case Control Consortium 2 (WTCCC2) project (GoDARTS and UKPDS et al., 2011), or by Illumina OmniExpress chips (3254 patients) funded by the Surrogate markers for Micro‐ and Macro‐vascular hard endpoints for Innovative diabetes Tools (SUMMIT) project (Fagerholm et al., 2012). Genotype data quality controls were undertaken using the protocols that were established for the WTCCC2 studies (GoDARTS and UKPDS et al., 2011) and the SUMMIT studies (Fagerholm et al., 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GoDARTS diabetic individuals were genotyped by either Affymetrix SNP6.0 chips (3673 patients) funded by the Wellcome Trust Case Control Consortium 2 (WTCCC2) project (GoDARTS and UKPDS et al., 2011), or by Illumina OmniExpress chips (3254 patients) funded by the Surrogate markers for Micro‐ and Macro‐vascular hard endpoints for Innovative diabetes Tools (SUMMIT) project (Fagerholm et al., 2012). Genotype data quality controls were undertaken using the protocols that were established for the WTCCC2 studies (GoDARTS and UKPDS et al., 2011) and the SUMMIT studies (Fagerholm et al., 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Genotype data quality controls were undertaken using the protocols that were established for the WTCCC2 studies (GoDARTS and UKPDS et al., 2011) and the SUMMIT studies (Fagerholm et al., 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Examples from T2D research highlight the diverse routes by which human genetics can inform translational medicine: (1) the combination of common-variant GWASs and candidate-gene resequencing has demonstrated that loss-of-function mutations in SLC30A8 (MIM: 611145; encoding a zinc transporter expressed in pancreatic islets) are protective for T2D, leading to efforts by several pharma companies to develop ZnT-8 antagonists; 93 (2) the use of genetic variants as instruments that ''simulate'' variation in environmental and biochemical exposures has clarified the extent to which vitamin D intake, early nutrition, circulating lipid levels, and chronic inflammation play causal roles with respect to the development of T2D [94][95][96][97][98] and has defined the relationship between insulin resistance and the distribution of adipose tissue; 99 (3) the identification of genetic variants associated with individual variation in response to commonly used therapeutic agents has refined our understanding of the mechanisms through which those agents operate 100,101 and, in some instances, has led to therapeutic optimization on the basis of genetic and/or clinical phenotype; 102 and (4) the combination of -omic measurements, longitudinal clinical phenotypes, and GWAS data has highlighted sets of molecules (e.g., branched-chain amino acids) that not only are prospectively associated with T2D progression but could also play a causal role in T2D development and thereby provide valuable clinical tools for stratification and prognostication. 103,104 Auto-immune Diseases Variant and Gene Discovery.…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…A variant in ATM has been shown to affect the glycemic response of metformin, and adenosine monophosphate-activated protein kinase (AMPK), a mediator of metformin action, may be regulated by ATM (33). Based on this observation, we elected to treat our patients with metformin, with good response.…”
Section: Articlesmentioning
confidence: 99%